Fabrication and Assessment of Diosgenin Encapsulated Stearic Acid Solid Lipid Nanoparticles for Its Anticancer and Antidepressant Effects Using in vitro and in vivo Models - Khan, Hina; Nazir, Sadia; Farooq, Rai Khalid; Khan, Ishaq N.; Javed, Aneela (Frontiers in Neuroscience, 2022)
Depression confers increased mortality and poor treatment outcomes in the oncology setting. Inflammatory cascade plays a pivotal role in the onset and progression of major depressive disorder (MDD) and Glioblastoma multiforme. Therefore, questing natural compounds with anti-inflammatory activity such as diosgenin can be more beneficial, acting as a double-edged sword targeting cancer and cancer-induced inflammation at the same time. The blood-brain barrier affects the transport of drugs to the central nervous system, thus limiting the therapeutic efficiency against intracranial pathologies such as a brain tumor. Encapsulating a drug molecule in lipid nanoparticles can overcome this obstacle and can deliver drugs across the blood-brain barrier. The current study has thus investigated the anticancer and antidepressant effect of TWEEN 80 (P80) coated stearic acid solid lipid nanoparticles (SLNP) encapsulated diosgenin. Diosgenin encapsulated P80 coated SLNPs were formulated using the solvent evaporation method and characterized by scanning electron microscopy (SEM), fourier transform infrared spectroscopy (FTIR), zero energy thermo-nuclear assembly (ZETA) potential, and X-ray diffraction (XRD) analysis. Spherical-shaped 20nm-200nm nanoparticles with the zeta potential -26.0 mV indicating high stability and formulation showed monodispersity. Drug entrapment and release of diosgenin from 1mg SLNPs was 61% and increased up to 90% as the concentration of SLNPs was increased, indicating direct proportionality with concentration. The cytotoxic effects of diosgenin encapsulated SLNPs were evaluated by in vitro cytotoxicity assay using a U-87 cell line. The IC50 value of the diosgenin was 194.4µM, while diosgenin encapsulation in nanoparticles slightly decreases the toxicity. After establishing a safety profile, antidepressant effects of encapsulated and non-encapsulated diosgenin were comprehensively evaluated in the Concanavalin-A induced sickness behavior mouse model. Our results indicate that diosgenin and diosgenin encapsulated nanoparticles alleviated anxiety-like and depressive behavior, as evident from the forced swim test, tail suspension test, and sucrose splash test. Diosgenin and diosgenin nanoparticles also improved grooming behavior and social interaction. Diosgenin incorporated SLNPs showed no significant rise in levels of neutrophils and leukocytes in mice. In conclusion, diosgenin and diosgenin encapsulated solid lipid nanoparticles proved successful in decreasing cancer cell proliferation and improving behavioral phenotype and merit further exploration.